Effect of MPS concentration on ripening kinetics and structural properties of CdS quantum dots in self-assembled thin films - Koc, Kenan (ELSEVIER, 2015)
The colloidal CdS quantum dots (QDs) were synthesized with various molar ratios of 3-mercaptopropyltrimethoxysilane (MPS) molecules. The results show that the smaller size of CdS QDs was obtained at the higher molar concentration of MPS. Sol gel spin coating method was used for deposition of the colloidal nanoparticles on a glass substrate. One pot production method was used to obtain self-assembled thin films of CdS QDs in SiO2 network and the grow kinetics of QDs were investigated. The samples were heat treated at various temperatures to observe the growth of the QDs. The sizes of the QDs were obtained in the range of 2-5 nm depending on the capping agent concentration and heat-treatment temperature. The activation energies for the Ostwald ripening process were found as 38.7, 56.4, 93,1 and 98.6 kJ/mol for the samples containing molar ratio of MPS:Cd = 0.25, 0.50, 1.00 and 2.00 respectively. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: CdS quantum dots; 3-Mercaptopropyltrimethoxysilane; SiO2; Ripening kinetics; Self-assembled; Thin film; OPTICAL-PROPERTIES; GROWTH-KINETICS; SIZE; BEHAVIOR; OXIDE; Chemistry